The other end of the needle : continuity and change among tattoo workers - Lane, David C. (Writer on tattooing) (Inequality at work: perspectives on race, gender, class, and labor, 2021)
"The Other End of the Needle demonstrates that tattooing is more complex than simply the tattoos that people wear. Using qualitative data and an accessible writing style, sociologist Dave Lane explains the complexity of tattoo work as a type of social activity. His central argument is that tattooing is a social world, where people must be socialized, manage a system of stratification, create spaces conducive for labor, develop sets of beliefs and values, struggle to retain control over their tools, and contend with changes that in turn affect their labor. Earlier research has examined tattoos and their meanings. Yet, Lane notes, prior research has focused almost exclusively on the tattoos-the outcome of an intricate social process-and have ignored the significance of tattoo workers themselves. "Tattooists," as Lane dubs them, make decisions, but they work within a social world that constrains and shapes the outcome of their labor-the tattoo. The goal of this book is to help readers understand the world of tattoo work as an intricate and nuanced form of work. Lane ultimately asks new questions about the social processes occurring prior to the tattoo's existence"--